Integrating artificial intelligence in STEM education: Enhancing learning through smart technologies - McDaniel, Angela (American Journal of STEM Education, 2025)
This paper explores integrating innovative technologies, including Mola Structural Kits, Smart Lab shake tables, and Micro: bit AI tools, to enhance STEM education through a project-based seismic engineering lesson plan. Students design, construct, and test earthquake-resistant structures by combining hands-on learning with smart classroom technologies. The approach emphasizes critical thinking, collaboration, and problem-solving, allowing students to bridge theoretical concepts with practical applications. This study highlights the benefits of interactive and data-driven learning environments, demonstrating how these tools improve engagement, deepen understanding of engineering principles, and develop essential skills for the 21st-century workforce.